The last urban frontier—assessing hotspots of urban change associated with LCLUC in Africa - Melinda Laituri; Orion S. E. Cardenas-Ritzert; Jody C. Vogeler; Shahriar Shah Heydari; Melissa R. McHale (Frontiers in Sustainable Cities)
Urbanization is one of the leading drivers of Land Cover Land Use Change (LCLUC) globally, and African countries are at the forefront of urban expansion trends, specifically in small and medium sized cities. Multiresolution spatial datasets can be used to guide sustainable urban management and assess progress towards the U.N. Sustainable Development Goals (SDGs), specifically SDG 11.3.1 indicator (the relationship between land consumption rate and population growth rate) to track urban change. We present a two-tiered land imaging approach identifying urban change hotspots in three African countries between 2016 and 2020 and characterize urban expansion in three secondary cities that have an SDG 11.3.1 indicator ratio greater that two (Mekelle, Ethiopia; Polokwane, South Africa, Benin City, Nigeria). This ratio indicates that land consumption outpaces population growth where patterns of urban expansion include leapfrog development, infill, and corridors revealing a dynamic urban expansion that outpaces administrative boundaries. We propose a “pixels to people” approach that defines not only urban form but includes urban function in secondary cities at multiple spatial scales where fine resolution depictions and local engagement create more robust, comprehensive datasets for urban planning.